Application of the Transtheoretical Model to Physical Activity and Health-related Quality of Life Among Older People Living With Frailty in the Community: The Fitness and Nutrition Program for Seniors (FANS) Study Protocol (International Journal of Studies in Nursing, 2024)
Background: When the COVID-19 pandemic is combined with frailty, not only are older people's types of activities and willingness to be active limited, but also issues and hidden concerns about health care arise. However, the effectiveness of health promotion strategies incorporating remote care technologies remains to be explored. Therefore, the purpose of this study was to develop a hybrid learning approach based on a fitness and nutrition program for seniors (FANS). Simultaneously, the FANS follows the Transtheoretical Model (TTM) as an overall framework to design blended learning in in-person and telecare modalities for older people living with frailty in the community. Methods: This study is a non-randomized, control-group, pretest–postest design. A total of 84 older participants living with frailty will be assigned to two groups. The intervention group will receive the 6-month, 9-session FANS through hybrid learning, which includes in-person physical activity (PA) training, nutritional guidance led by a nurse, and group discussions. The official account of the FANS and the group chat will provide individuals with online home practice at the current TTM stage, session time and home practice reminders, video reviews, consultations, and tutoring for telecare. The waitlist control group will maintain regular health promotion activities. Three repeated assessments (one pre-test and two post-training tests conducted after 3 months and after 6 months) will be conducted. The primary outcome measures will include frailty status, PA, and health-related quality of life (HRQoL), and the secondary outcome measures will be health-related data. Statistical analysis will include the Chi-squared test, Independent Sample t-test, and Generalized Estimating Equation (GEE). Discussion: This study will provide evidence that the FANS for older people living with frailty will have more positive and beneficial outcomes than the traditional method. Simultaneously, we hope the FANS will help the older population living with frailty in the community to transform their health difficulties in the future. Trial Registration: NCT05242549. Registered 22 February 2022.